Plasma enhanced chemical vapour deposition of carbon nitride films from ethane and nitrogen gas mixtures / Maisara binti Othman - Othman, Maisara (2012)
The fabrication and characterization of amorphous carbon nitride a-CNx thin films are intensively studied in this work. These films were obtained using radio frequency (rf) plasma enhanced chemical vapour deposition. In the first part of this work, a-CNx films were deposited either from methane and nitrogen (CH4:N2) or ethane and nitrogen (C2H6:N2) mixtures under identical deposition conditions. The effects of varying the N2 flow rate in each mixture were studied. It was observed that the use of different hydrocarbon gas produce either graphitic or polymeric a-CNx films. It was found that each set of films demonstrate its own unique characteristic. For films produced from CH4:N2, the sp2 clusters increased due to high N incorporation into the films. This leads to the formation of graphitic-like structure. The nitrogen also distorts the carbon network and induced the increase in nitrile and/or isonitrile C≡N bonds. This bonding influences the structure of the films by becoming more disordered and more porous. In contrast, low nitrogen incorporation was observed for films produced from C2H6:N2 mixture. In these films, CHn bonds are preferred which leads to the formation of more sp3 sites in the films. This results in the films having higher Eg (2.8 eV) compared to films deposited from CH4:N2 which exhibits average Eg values of 1.9 eV. The increase in CHn bonds indicates high H content which was found to be approximately 50 a.t%. This value suggests the films to be polymeric-like a-CNx films. A significant increase in PL intensity with increase in N incorporation was observed from both sets of films. However, the PL intensity of films produced from C2H6:N2 is generally higher compared to films produced from CH4:N2. From these results it seems that the C2H6:N2 mixture may be a better alternative to the popular CH4:N2, as it shows a significantly higher PL emission and low porosity. The disadvantage is the lower growth rate and N incorporation of the films formed using C2H6:N2 mixture. In order to solve these problems and further improve the properties of these films, hydrogen were introduced into the C2H6:N2 mixture. As a result, the films produced from C2H6:N2:H2 shows enhancement in their growth rate and N incorporation with the increase in hydrogen dilution. Increase of the film‟s growth rate and N incorporation, while retaining low porosity and high PL properties was possible if low H2 dilution was applied. At high H2 dilution, N incorporation increases but this leads to the increase in porosity and quenching of the PL intensities of the films. However, even the PL efficiency decreases, these films still generally exhibit much higher PL emission intensities compared to those CH4:N2. This work concludes that the C2H6:N2:H6 mixture with low H2 dilution is an excellent alternative to the popular CH4:N2 mixture in the deposition of rf PECVD CNx films to obtain high PL intensities, high N incorporation and low porosity.